Advertisement Remove all ads

Prove that : X^(A(B - C))/X^B(A - C) ÷ ((X^B)/(X^A))^C = 1 - Mathematics

Sum

Prove that :
`[ x^(a(b - c))]/[x^b(a - c)] ÷ ((x^b)/(x^a))^c = 1`

Advertisement Remove all ads

Solution

We need to prove that
`[ x^(a(b - c))]/[x^b(a - c)] ÷ ((x^b)/(x^a))^c = 1`

LHS =

= `x^[a(b - c ) - b( a - c )] ÷ x^(bc)/x^(ac)` 

= `x^( ab - ac - ab + bc ) ÷ x^( bc - ac )`

= `x^( ab - ac - ab + bc - bc + ac )`
= `x^0`
= 1
= RHS

Concept: Solving Exponential Equations
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 9 ICSE
Chapter 7 Indices (Exponents)
Exercise 7 (B) | Q 7.2 | Page 100
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×